Bending behavior of octet-truss lattice structures: Modelling options, numerical characterization and experimental validation. (July 2021) - Korshunova, N.; Alaimo, G.; Hosseini, S.B.; Carraturo, M.; Reali, A.; Niiranen, J.; Auricchio, F.; Rank, E.; Kollmannsberger, S.
Graphical abstract: Highlights: Process-induced defects affect the mechanical behavior of AM octet-truss lattices. An immersed image-based workflow efficiently incorporates as-manufactured geometries. CT-based numerical results show an excellent agreement with experimental data. A flexible framework includes high-order continuum theories to account for size effects. Abstract: Selective Laser Melting (SLM) technology has undergone significant development in the past years providing unique flexibility for the fabrication of complex metamaterials such as octet-truss lattices. However, the microstructure can exhibit significant variations due to the high complexity of the manufacturing process. Consequently, the mechanical behavior, in particular, linear elastic response, of these lattices is strongly dependent on the process-induced defects, raising the importance on the incorporation of as-manufactured geometries into the computational structural analysis. This, in turn, challenges the traditional mesh-conforming methods making the computational costs prohibitively large. In the present work, an immersed image-to-analysis framework is applied to efficiently evaluate the bending behavior of AM lattices. To this end, we employ the Finite Cell Method (FCM) to perform a three-dimensional numerical analysis of the three-point bending test of a lattice structure and compare the as-designed to as-manufactured effective properties. Furthermore, we undertake a comprehensive study on the applicability of dimensionally reduced beam models to the prediction of the bending behavior of lattice beams and validate classical and strain gradient beam theories applied in combination with the FCM. The numerical findings suggest that the octet-truss lattices exhibit size effects, thus, requiring a flexible framework to incorporate high-order continuum theories.